The gene expression landscape of pine seedling tissues. (4th August 2017) - Cañas, Rafael A.; Li, Zhen; Pascual, M. Belén; Castro‐Rodríguez, Vanessa; Ávila, Concepción; Sterck, Lieven; Van de Peer, Yves; Cánovas, Francisco M.
Summary: Conifers dominate vast regions of the Northern hemisphere. They are the main source of raw materials for timber industry as well as a wide range of biomaterials. Despite their inherent difficulties as experimental models for classical plant biology research, the technological advances in genomics research are enabling fundamental studies on these plants. The use of laser capture microdissection followed by transcriptomic analysis is a powerful tool for unravelling the molecular and functional organization of conifer tissues and specialized cells. In the present work, 14 different tissues from 1‐month‐old maritime pine ( Pinus pinaster ) seedlings have been isolated and their transcriptomes analysed. The results increased the sequence information and number of full‐length transcripts from a previous reference transcriptome and added 39 841 new transcripts. In total, 2376 transcripts were ubiquitously expressed in all of the examined tissues. These transcripts could be considered the core 'housekeeping genes' in pine. The genes have been clustered in function to their expression profiles. This analysis reduced the number of profiles to 38, most of these defined by their expression in a unique tissue that is much higher than in the other tissues. The expression and localization data are accessible at ConGenIE.org (http://v22.popgenie.org/microdisection/ ). This study presents an overview of the gene expression distribution in different pine tissues, specifically highlighting the relationships between tissue gene expression and function. This transcriptome atlas is a valuable resource for functional genomics research in conifers. Significance Statement: In the present work, a gene expression atlas from tissues of maritime pine was generated using laser capture microdissection and next generation sequencing. The main results are accessible at ConGenIE.org (http://congenie.org/ ). This public information will facilitate future studies in conifer genomics.